2015
DOI: 10.15309/15psd1603010
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Alcohol Consumption in Adolescence, by Gender

Abstract: ___________________________________________________________________________ RESUMO:De acordo com o último relatório do ESPAD (2012), 74% dos adolescentes portugueses reportaram ter consumido bebidas alcoólicas no último ano, 52% no último mês e 22% reportaram "binge drinking". O consumo de álcool é um problema grave e prevalente entre os jovens, sendo indispensável identificar fatores associados a este consumo, por forma a desenvolver estratégias preventivas eficazes. Objetivos: Descrever as perceções sobre os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
4
0
6
Order By: Relevance
“…Cient., v. 23, n. 1, p. 72-94 jan./jun. 2018 (ISSNe 2237-9010) Conforme tais relatos, em pesquisa realizada no ano de 2007 pela Secretária Nacional Antidrogas, a impulsividade no consumo do álcool e a prática do 'binge drink' altera o comportamento do indivíduo, podendo acontecer importantes modificações neurofisiológicas, tais como a desinibição comportamental, comprometimento cognitivo, diminuição da atenção, piora da capacidade de julgamento, diminuição da coordenação motora, custos sociais e de saúde, gerando acidentes, violência (sexual, física, verbal, doméstica), homicídio e roubo (BRITO et al, 2015;LEMOS;ZALESKI, 2004).…”
Section: Discussão Dos Resultadosunclassified
See 1 more Smart Citation
“…Cient., v. 23, n. 1, p. 72-94 jan./jun. 2018 (ISSNe 2237-9010) Conforme tais relatos, em pesquisa realizada no ano de 2007 pela Secretária Nacional Antidrogas, a impulsividade no consumo do álcool e a prática do 'binge drink' altera o comportamento do indivíduo, podendo acontecer importantes modificações neurofisiológicas, tais como a desinibição comportamental, comprometimento cognitivo, diminuição da atenção, piora da capacidade de julgamento, diminuição da coordenação motora, custos sociais e de saúde, gerando acidentes, violência (sexual, física, verbal, doméstica), homicídio e roubo (BRITO et al, 2015;LEMOS;ZALESKI, 2004).…”
Section: Discussão Dos Resultadosunclassified
“…Ao questionar sobre o conhecimento dos malefícios trazidos pelo consumo de bebidas alcoólicas, foi consenso que o grupo afirmou conhecer e mesmo assim optam por continuar bebendo.4.4 DE RUIM? SÓ A RESSACAAo questionar as entrevistadas sobre as ocasiões em que costumam consumir bebidas alcoólicas, pode-se verificar que o consenso do grupo foi que não existe uma ocasião específica, pois consideram que todas são favoráveis para realizar tal prática:SegundoBrito et al (2015) o consumo de bebidas alcoólicas é visto pelos jovens como algo natural, como um momento de diversão que os permite fugir dos Ágora: R. Divulg. Cient., v. 23, n. 1, p. 72-94 jan./jun.…”
unclassified
“…It was proposed a training practice capable of enhancing permanent education workshops as moments of shared construction of knowledge. The objective of this preliminary PAPS workshop was to equip the research team with the participatory action research approach to health, convergent methodologies and group activities using the World Café methodology (9) , which consists of a conversation technique, very close to the Focus Group and that simulates the environment of a cafe, oriented based on a theme, facilitating constructive involvement in complex issues. The World Café was only used in this workshop with the group of researchers and scholars.…”
Section: The Starting Pointmentioning
confidence: 99%
“…It is also important to consider the social context (family and peers), the community (pro-alcohol attitudes, incentive, and availability of the product), the society (influence of the media on adolescents) and individual characteristics when explaining alcohol consumption behavior (Muisener, 1994). Brito et al (2015) identified family attitudes towards alcohol consumption and negative emotions management as risk factors for early experimentation and regular alcohol consumption among university students. Thus, it is crucial to implement effective health education programmes to prevent alcohol use among adolescents.…”
mentioning
confidence: 99%
“…This programme was created and structured based on the existing literature about risk factors associated with alcohol consumption, susceptible of being modified by a school-based intervention (Brito et al, 2015;Magalhães & Precioso, 2011). The intervention was also inspired by the "Smokeout II" prevention programme for students attending the 9th grade (Sousa et al, 2017) and by the "Prevención del consumo de alcohol y tabaco" prevention programme (Hernández et al, 1999).…”
mentioning
confidence: 99%